1981
DOI: 10.1111/j.1365-2125.1981.tb01154.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the effects of propranolol and oxprenolol on forearm blood flow and skin temperature.

Abstract: 1 The effects of oxprenolol 80 mg and propranolol 80 mg on resting forearm blood flow (RFBF) and skin temperature were compared in seven normotensive subjects, for 4 h after an oral dose. 2 There was a significant fall of RFBF after propranolol (mean + s.e. mean 0.74 ± 0.24 ml 100 g-' min-1) compared to a smaller non-significant reduction after oxprenolol (0.35 + 0.19 ml 100 g-' min-'). Propranolol produced a greater fall in heart rate than oxprenolol at all times except at 2.5 h.Three subjects experienced fal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These long-term effects of Padrenoceptor blockers with ISA are most pronounced during treatment with pindolol (Gebhardt, 1968;Lang & Holtman, 1974;Kuramato et al, 1974;Klein et al, 1976;Tsukiyama et al, 1976;Zamora et al, 1975;Atterhog, Duner & Pemow, 1976;Atterhog et al, 1977aAtterhog et al, , 1977bSavenkov etal., 1977;Velasco et al, 1980) but similar, albeit smaller, alterations have been reported after practolol (Bodem et al, 1973), oxprenolol (Wilson et al, 1968;Taylor et al, 1970;Tsukiyama et al, 1976) and alprenolol (Lund-Johansen & Ohm, 1976;Frisk-Holmberg et al, 1977). In addition lower forearm vascular resistances have been reported to be less during treatment with acebutolol (Ireland & Littler, 1981), oxprenolol (Vandenburg et al, 1981) and pindolol (Atterhog et al, 1976;Svendsen et al, 1981) as compared to treatment with propranolol. In fact the inverse correlation between changes in cardiac output and changes in vascular resistance which was found after short-term P-adrenoceptor blockade, is essentially unaltered during long-term (Figure 3); it is only shifted to a lower level of vascular resistance.…”
Section: Introductionmentioning
confidence: 74%
“…These long-term effects of Padrenoceptor blockers with ISA are most pronounced during treatment with pindolol (Gebhardt, 1968;Lang & Holtman, 1974;Kuramato et al, 1974;Klein et al, 1976;Tsukiyama et al, 1976;Zamora et al, 1975;Atterhog, Duner & Pemow, 1976;Atterhog et al, 1977aAtterhog et al, , 1977bSavenkov etal., 1977;Velasco et al, 1980) but similar, albeit smaller, alterations have been reported after practolol (Bodem et al, 1973), oxprenolol (Wilson et al, 1968;Taylor et al, 1970;Tsukiyama et al, 1976) and alprenolol (Lund-Johansen & Ohm, 1976;Frisk-Holmberg et al, 1977). In addition lower forearm vascular resistances have been reported to be less during treatment with acebutolol (Ireland & Littler, 1981), oxprenolol (Vandenburg et al, 1981) and pindolol (Atterhog et al, 1976;Svendsen et al, 1981) as compared to treatment with propranolol. In fact the inverse correlation between changes in cardiac output and changes in vascular resistance which was found after short-term P-adrenoceptor blockade, is essentially unaltered during long-term (Figure 3); it is only shifted to a lower level of vascular resistance.…”
Section: Introductionmentioning
confidence: 74%
“…This raises the question of whether propranolol exerts its effect via vasoconstriction of the high-flow blood vessels feeding the IH tumor. Propranolol has been shown to decrease blood flow to many tissues following single administration (Nies et al 1973;McSorley and Warren 1978;Vandenburg et al 1981). Particularly in the skin, adrenaline-induced vasoconstriction has been shown to be increased by oral propranolol (Doshi et al 1984).…”
Section: Hemodynamic Effectsmentioning
confidence: 99%
“…If beta blockers are administered when bronchi are under the effect of beta, stimulation-that is, in the asthmatic during an attack-there is no evidence that partial agonist activity confers any benefit.37 In blood vessels partial agonist activity is of no importance in modifying beta blocking effects on muscle blood flow during exercise, though at rest a beta blocker with partial agonist activity may have less effect on decreasing forearm blood flow than a beta blocker without this property. 38 Published clinical reports can be culled to produce many interpretations of the importance of partial agonist activity. In hypertension two comparative studies using maximal doses showed that propranolol (which does not possess partial agonist activity) produced a 3-4 mm Hg greater fall in supine and standing blood pressure than oxprenolol (which does possess partial agonist activity).39 Furthermore, a paradoxical increase in blood pressure may occur with the use of larger doses of beta blockers with more marked partial agonist activity-for example, pindolol.4' One might predict that partial agonist activity might detract from the antianginal properties of a beta blocker.…”
Section: Partial Agonist Activitymentioning
confidence: 99%
“…44 4 There is evidence that beta blockers possessing partial agonist activity are less likely to cause cold hands and feet and worsen Raynaud's phenomenon, and this property appears to be more important than cardioselectivity in determining skin blood flow. 38 The effects on exercise capacity are less clear, and good comparative data are needed on the long term effects of various beta blockers on blood flow in the limbs. Beta blockers have recently been shown to increase plasma triglycerides, decrease concentrations of high density lipoproteins and increase concentrations of low density lipoproteins.46 These changes may constitute a coronary risk factor.…”
Section: Partial Agonist Activitymentioning
confidence: 99%